The Ability of Posters to Enhance the Comfort Level with Breastfeeding in a Public Venue in Rural Newfoundland and Labrador. (February 2016) - Vieth, Alissa; Woodrow, Janine; Murphy-Goodridge, Janet; O'Neil, Courtney; Roebothan, Barbara
Background: The acceptance and support of breastfeeding in public venues can influence breastfeeding practices and, ultimately, the health of the population. Objective: The primary aim of this study was to investigate whether posters targeted at the general public could improve acceptability of breastfeeding in public places. Methods: A convenience sample of 255 participants was surveyed at shopping centers in 2 rural communities of Newfoundland and Labrador. Experimentally, questions were posed to 117 participants pre- and post-exposure to 2 specific posters designed to promote public acceptance of breastfeeding in public. Results: Initially, we surveyed that only 51.9% of participants indicated that they were comfortable with a woman breastfeeding anywhere in public. However, context played a role, whereby a doctor's office (84.5%) or park (81.4%) were the most acceptable public places for breastfeeding, but least acceptable was a business office environment (66.7%). Of participants, 35.4% indicated previously viewing specific posters. We used a visual analog scale to test poster viewing on the acceptability of public breastfeeding in the context of a doctor's office and a restaurant. Results of pre- versus post-viewing of the promotional posters indicated significant improvements in both scenarios: in a doctor's office ( P = .035) and in a restaurant ( P = .021). Conclusion: Nearly 50% of the surveyed population indicated discomfort with a mother breastfeeding in public. Both cross-sectional and interventional evidence showed that posters significantly improved the reported level of comfort toward seeing breastfeeding in public.